Assessment of Carbon Storage and Ecological Functions of Beach Sheoak (Casuarina equisetifolia) in Muara Cemara, Pantai Panjang, Bengkulu City - Anggraini, Putri Lisya; Darmi; Rizwar; Wati, Meliya; Norfahmi, Siti H. (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to estimate the aboveground biomass, carbon stock, and carbon dioxide (CO₂) sequestration of coastal she-oak (Casuarina equisetifolia) stands in Muara Cemara, Pantai Panjang, Bengkulu City, and to describe their ecological functions based on field observations. The study was conducted in September 2025 using a non-destructive method based on the allometric equation ln Y = –2.177 + 2.523(ln DBH). Data were collected from 17 systematically established plots, each measuring 20 m × 20 m. The results showed that the stands had an aboveground biomass of 2.37 ± 0.63 t ha⁻¹, a carbon stock of 1.09 ± 0.20 t C ha⁻¹, and CO₂ sequestration of 4.01 ± 1.06 t CO₂ ha⁻¹. The 21–30 cm diameter class contributed the largest proportion of total biomass and carbon stock, indicating the important role of medium-sized trees in carbon accumulation. Ecologically, C. equisetifolia may contribute to reducing coastal erosion, stabilizing sandy substrates, improving microhabitat conditions, and supporting coastal habitat functions. These findings indicate that C. equisetifolia stands have potential as a complementary component of coastal carbon storage, climate change mitigation, and ecosystem-based coastal management in sandy coastal environments.